Structural basis for distinct inflammasome complex assembly by human NLRP1 and CARD8 - Qin Gong (Nature Portfolio, 2021)
NLRP1 and CARD8 are two recently described sensor proteins for the human inflammasome complex. Here, the authors present the cryo-EM CARD filament structures of the NLRP1 and CARD8 activating domains, which reveal how NLRP1 and CARD8 discriminate between ASC and pro-caspase-1. They further propose a two-step model for NLRP1 activation.